Using community‐based participatory research methods to inform care for patients experiencing homelessness: An opportunity for resident education on health care disparities. (29th September 2021) - Ryus, Caitlin R.; Yang, David; Tsai, Jennifer; Meldrum, Jonathan; Ngaruiya, Christine
Abstract: People experiencing homelessness (PEH) suffer higher burdens of chronic illnesses, have higher rates of emergency medicine (ED) use and hospitalization, and ultimately are at increased risk for premature death compared to housed counterparts. Structural racism contributes to a disproportionate burden of homelessness among people of color. PEH experience not only significant medical concerns but also complex social needs that need to be addressed concurrently for effective healing, issues that have been magnified by the COVID‐19 pandemic. As health disparities and structural racism intersect among PEH, it is critically important to develop PEH‐centered interventions to improve care and health outcomes as part of an effort to dismantle racism. One opportunity to address these disparities in care for PEH is through training ED physicians on methods for identifying and intervening on the unique needs of vulnerable patient groups. The Accreditation Council for Graduate Medical Education has outlined health quality pathways in the clinical learning environment to address health disparities. Community‐based participatory research (CBPR) is particularly well suited for this scenario as it allows experiential learning for trainees to work with and understand a diverse group of stakeholders, to deepen their knowledge of local health disparities, and to lead research and measure outcomes of interventions to tackle health disparities. In this paper, we highlight the utility of CBPR in fostering experiential learning for EM residents on tackling health disparities and the importance of community collaboration in trainee‐led interventions for comprehensive ED care.